A new republic of lawyers? Legal careers, state power, and political change in contemporary Brazil. Issue 3 (3rd July 2017) - de Sa e Silva, Fabio
ABSTRACT: The literature on political science and public policy offers many explanations for why legal professionals can come to the forefront of political processes, as it has remarkably happened in the current Brazilian crisis. Building on a political sociology approach, namely that set forth by Bourdieu, I treat the legal profession and the state as interconnected 'fields' and find three signs of change in their co-structuration in post-1988 Brazil. These findings shed new light on the public prominence of figures like Sergio Moro, Deltan Dallagnol, and Julio Marcelo de Oliveira and the emergence of what appears to be a 'new Republic of Lawyers'. Yet, they also pose questions and concerns about the risk this represents to the sustainability of democratic politics in that country.